FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI KELURAHAN KAMPUNG BUGIS KOTA TANJUNGPINANG TAHUN 2014 - Dewi Pusparianda (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Health problems greatly influenced by behavioral factors and environmental factors. One of the diseases based on an unhealthy environment is diarrhea. Environmental sanitation and personal hygiene are less healthy will facilitate contracting the disease agents that cause diarrhea. This study aims to identify factors associated with the incidence of diarrhea in infants in Kampung Bugis Tanjungpinang 2014. Type of analytical research and observational methods Case control study design. Study subjects were sampled of 46, (23 cases and 23 controls). Sampling was conducted by consecutive sampling. Statsistik analysis using chi square test. The results showed 67.4% use clean water that meets the requirements; 58.7%, had the habit of washing hands; 67.4% of healthy latrine use and 65.2% who do hygiene sanitation food properly. Results of statistical test Chi-Square on bivariate analysis showed no relationship fresh water use (p = 0.000); handwashing (p = 0.000); healthy latrine (p = 0.011) and food sanitation hygiene (p = 0.005) and the incidence of diarrhea. From the above results, it is necessary to motivate the community outreach effort in the procurement and use of clean water that meets the requirements, good hand washing habits, and the use of latrines are eligible.